Sin (A-B)=SinACosB-CosASinB
Answers
Answered by
0
what you want plz describe
Answered by
3
let A = 60 , B = 30
lhs = sin (A-B) = sin(60-30) = sin 30 =1/2
rhs = sinAcosB-cosAsinB
= sin60cos30 - cos60sin30
= √3/2 *√3/2 - 1/2*1/2
= 3/4 -1/4
=(3-1)/4
=2/4
=1/2
therefore
lhs =rhs
sin(A-B) = sinAcosB - cosAsinB
lhs = sin (A-B) = sin(60-30) = sin 30 =1/2
rhs = sinAcosB-cosAsinB
= sin60cos30 - cos60sin30
= √3/2 *√3/2 - 1/2*1/2
= 3/4 -1/4
=(3-1)/4
=2/4
=1/2
therefore
lhs =rhs
sin(A-B) = sinAcosB - cosAsinB
Similar questions
History,
9 months ago
Social Sciences,
9 months ago
History,
1 year ago
Science,
1 year ago
Math,
1 year ago